HUBUNGAN PENGETAHUAN DAN SIKAP PERAWAT DENGAN KEPATUHAN PENGGUNAAN ALAT PERLINDUNGAN DIRIPADA MASA PANDEMI COVID-19 - Esti Nur Janah; Eva Diana Sari (LPPM ITEKES Mahardika, 2021)
The first COVID-19 case in South Brebes was in the Paguyangan Community Health Center area, which originated from the Gowa cluster. One of the efforts that can be used to stop the transmission of COVID-19 is to use PPE (Personal Protective Equipment). The knowledge of medical personnel regarding the use of PPE when handling COVID-19 is important as a way to prevent transmission from COVID-19 patients to medical personnel. This study aims to determine the relationship between knowledge and attitudes of nurses and compliance with the use of personal protective equipment (PPE) during the coronavirus disease pandemic at Paguyangan Public Health Center in 2020. The design of this study is a correlation analysis with a cross sectional approach using total sampling method and 32 nurses were obtained as a sample. Data collection began in October-December 2020. The questionnaire used consisted of a questionnaire about Covid-19 knowledge and a questionnaire about nurses' attitudes in using PPE, each with 20 question items. To assess the adherence of nurses using the WHO adherence checklist for use of PPE adaptation. The results of the analysis showed that there was a significant relationship between knowledge of nurses and adherence to the use of PPE with a value of p = 0.021 (p <0.05) and a significant value of the relationship between nurses' attitudes and compliance with the use of PPE during the Covid-19 pandemic at the Paguyangan Health Center in 2020. p = 0.017 (p <0.05). So it can be concluded that there is a significant relationship between attitudes and compliance with nurses at Paguyangan Health Center. The results of this study can be used as a reference for nurse credentialing in the use of ADP and for further research, research can be carried out by adding variables such as length of service, availability of facilities, level of nurse education and supervision of the use of PPE.